2022
DOI: 10.1002/fsn3.2912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid fermentation on the nutritional quality and consumer acceptability of African nightshade

Abstract: African nightshade (ANS) is among many underexploited and neglected indigenous vegetables. This study assessed the effect of lactic acid fermentation (LAF) on nutritional and sensory quality in Solanum villosum (Sv) and Solanum scabrum (Ss). Spontaneously fermented (SF) and controlled fermented (CF) conditions using Lactobacillus plantarum LP90 and Leuconostoc mesenteroides LM58 were employed for 15 days and 120 h. From the fermented pickles, relish products were prepared using cooking oil and a variety of spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…It was also reported that pH strongly affected the degradation of vitamin C, so that vitamin C was most stable at pH 3.5 and least stable at pH 5.5 [38]. These achievements are consistent with the results of Sangija et al [40], who showed a substantial decrease in the vitamin C content of African nightshade during controlled and spontaneous fermentation by Leuconostoc mesenteroides and L. plantarum. Similarly, different researchers detected vitamin C loss after the fermentation of lupini beans, cowpea, and pigeon pea [34,41,42].…”
Section: Bioactive Compoundssupporting
confidence: 88%
“…It was also reported that pH strongly affected the degradation of vitamin C, so that vitamin C was most stable at pH 3.5 and least stable at pH 5.5 [38]. These achievements are consistent with the results of Sangija et al [40], who showed a substantial decrease in the vitamin C content of African nightshade during controlled and spontaneous fermentation by Leuconostoc mesenteroides and L. plantarum. Similarly, different researchers detected vitamin C loss after the fermentation of lupini beans, cowpea, and pigeon pea [34,41,42].…”
Section: Bioactive Compoundssupporting
confidence: 88%
“…However, it has also been suggested that it may have health-promoting effects [265]. It has been shown that lectin, phytate, tannin, and oxalate levels decrease as a result of fermentation compared to fresh produce [266][267][268]. As a result of lactic acid fermentation in the African nightshade plant, the tannin level decreased by 76.27-92.88%, and the oxalate level decreased by 77.33-90% [267].…”
Section: Fermented Vegetablesmentioning
confidence: 99%
“…Increased the amounts of 3-caffeoylquinic, 4-caffeoylquinic and 5-caffeoylquinic acids, Ekaempferol-3-O-rutinoside, chlorogenic acid, caffeoylmalic acid and quercetin-3-O-xylosyl-rutinoside [14] Nightshade pickle and relish Fermentation Improved the β-carotene content of both products [186] Jew's mallow Cooking Improved mineral content (phosphorous, potassium, calcium, magnesium, sodium and micro minerals (iron, manganese, zinc)) of the leaves [187] Enhanced protein, ash and dietary (soluble and insoluble) fibre [187] Improved cellulose and hemicellulose of the leaves and enhanced essential amino acids except phenylalanine [187] Chinese cabbage Blanching in 5% lemon juice Increased total chlorophyll retention [128] Increased TPC, FRAP and TEAC [128] Improved quinic and ferulic acids [128] Improved levels of kaempferol-dihexoside, sinapoyl malate, rutin, isorhamnetin-O-dihexoside and kaempferol-3-O-hydroxyferuloyl-trihexoside in the leaves [128] Stir frying Improved levels of kaempferol-3-O-hydroxyferuloyl-trihexoside, kaempferol-dihexoside, sinapoyl malate, rutin and isorhamnetin-O-dihexoside [128] Fermentation Increased β-carotene content [188] Improved mineral content (iron, zinc, calcium, potassium, copper and nickel) [188] Pumpkin leaves Boiling Improved the bioaccessibility of most polyphenols apart from methylquinic acid, cis-4-feruloylquinic acid and phenethyl rutinoside [189] Stir frying…”
Section: Nightshade Solar Dryingmentioning
confidence: 99%